Accelerated growth programs for dairy calves - Michael J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2004)
Accelerated-growth feeding programs are the newest buzz word in calf rearing. Accelerated programs require a milk replacer containing more crude protein and less fat content than traditional milk replacers. These programs are generally phase-feeding programs that increase the amount of milk replacer as the calf advances in age. In addition, changes in the calf starter are necessary to achieve optimal performance. These programs increase weight gain during the liquid-feeding period and may positively impact calf health. Changes in the composition and amount of milk replacer used increase the cost of the accelerated program, compared with that of conventional programs. Gains achieved from an accelerated-growth program during the first few weeks of life are quickly lost if aggressive feeding and management programs are not followed through after weaning. Acceleratedgrowth calf programs are part of the total heifer rearing program to improve overall lactation efficiency by reaching optimal growth and age-at-first-breeding targets for dairy operations.; Dairy Day, 2004, Kansas State University, Manhattan, KS, 2004;
Keywords: Dairy Day; 2004; Kansas Agricultural Experiment Station contribution; no. 05-112-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 941; Dairy; Heifers; Calves; Accelerated growth